Measuring the Antioxidant Effect of Limnocharis Flava on Malondialdehyde Activities in Livers of Alloxan-induced Diabetic Rats - Yithro Serang; Virda Laili (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Antioxidants are substances counteracting the effects of free radicals. Antioxidants are formed in several forms, encompassing vitamins, minerals, and phytochemicals. Genjer or yellow velvet leaves (Limnocharis Flava) is an aquatic plant potentially beneficial alternative to natural antioxidants. This study aims to measure the antioxidant effect from the yellow velvetleaf ethanol extract on malondialdehyde (MDA) activities in livers of diabetic rats (Rattus novergicus) induced by alloxan in three different doses. The tested animals were randomly divided into five groups comprising six white rats previously induced with alloxan by intra-peritoneal injection. Group 1 was the negative control provided 0.5% CMC Na while group 2 was a positive control administered 0.45 mg glibenclamide. On the other hand, groups 3, 4, and 5 were the experimental groups that provided the extract of yellow velvetleaf as many as 32.5 mg/kg body weight (BW) ethanol, 65 mg/kg BW ethanol extract, and 130 mg/kg BW, respectively. Furthermore, the extracts were administered once on the 7th, 14th, and 21st days; the parameters observed were MDA activities in the rats’ livers. The Thiobarbituric Acid Reactive Substances (TBARs) method was then employed to investigate these actions. The one-way ANOVA was administered to examine the acquired data from the examination, followed by a post hoc test. The average points of the MDA level from group 1 to group 5 were 10.78 0.33, 3.71 + 0.19, 7.25 + 0.26, 5.76 + 0.25, and 4.01 + 0.22, correspondingly, according to the results. The one-way ANOVA test revealed that MDA levels in each test group were significantly different (p 0.05). Based on these findings, it may be concluded that feeding ethanol extract from yellow velvet leaves to diabetic rats reduces MDA levels in their livers, therefore preserving cells from harm.